2016
DOI: 10.1186/s12967-016-0959-9
|View full text |Cite
|
Sign up to set email alerts
|

Flow diverter effect of LVIS stent on cerebral aneurysm hemodynamics: a comparison with Enterprise stents and the Pipeline device

Abstract: BackgroundThe aim of this study was to quantify the effect of the new Low-profile Visualized Intraluminal Support (LVIS®D) device and the difference of fluid diverting effect compared with the Pipeline device and the Enterprise stent using computational fluid dynamics (CFD).MethodsIn this research, we simulated three aneurysms constructed from 3D digital subtraction angiography (DSA). The Enterprise, LVIS and the Pipeline device were virtually conformed to fit into the vessel lumen and placed across the aneury… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
148
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(153 citation statements)
references
References 37 publications
5
148
0
Order By: Relevance
“…Compromise of perforating arteries and consequent infarction because of struts coverage and delayed neointimal proliferation over the perforator ostia were the most common complications. Generally, porosity of the stent induces neck coverage and the possibility of flow stasis in the aneurysm, which plays an important role in thrombosis 14. The metal coverage rate of FDs was reported to be 30–40%.…”
Section: Discussionmentioning
confidence: 99%
“…Compromise of perforating arteries and consequent infarction because of struts coverage and delayed neointimal proliferation over the perforator ostia were the most common complications. Generally, porosity of the stent induces neck coverage and the possibility of flow stasis in the aneurysm, which plays an important role in thrombosis 14. The metal coverage rate of FDs was reported to be 30–40%.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is higher than that (8%) of an Enterprise (Cordis, Neurovascular, Miami, Florida, USA) as a laser-cut stent. 15) As the use of an LVIS stent in the cervical region is not covered by health insurance, it must be carefully operated. However, it has a high metallic coverage rate as a currently available stent.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has a high metallic coverage rate as a currently available stent. Wang et al 15) quantified hemodynamic changes related to stenting using computational fluid dynamics (CFD), and reported that the wall shear stress and velocity reduction rates when two LVIS stents were used were 63% and 46%, respectively, being higher than those of a Pipeline (51% and 37%, respectively). In addition, an LVIS stent makes it possible to intentionally increase the density of a cell on deployment.…”
Section: Discussionmentioning
confidence: 99%
“…5 Tateshima et al 19 investigated the alterations in intra-aneurysmal hemodynamics with the placement of high-porosity open-cell stents across the necks of aneurysms and found that the placement of a single Neuroform stent (Stryker Neurovascular) reduced the intra-aneurys- mal flow velocity by 22%-64%. In another study, Wang et al 20 assessed the hemodynamic changes inside aneurysms induced by the implantation of conventional stents and found that the velocity of the jet flow entering the aneurysm and wall shear stresses on the aneurysm were significantly reduced by the placement of a stent. 20 These authors suggested that the hemodynamic changes induced by stents promote thrombus formation inside the aneurysm and reduce the risk of aneurysm growth and rupture.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, Wang et al 20 assessed the hemodynamic changes inside aneurysms induced by the implantation of conventional stents and found that the velocity of the jet flow entering the aneurysm and wall shear stresses on the aneurysm were significantly reduced by the placement of a stent. 20 These authors suggested that the hemodynamic changes induced by stents promote thrombus formation inside the aneurysm and reduce the risk of aneurysm growth and rupture. Blankena et al 21 studied the correlation between wall shear stress and wall thickness of aneurysms with 7T MR imaging.…”
Section: Discussionmentioning
confidence: 99%